Cancer Recurrence Fear and Return to Work in Breast Cancer Survivors:The Mediating Effects of Health Literacy - Zhu X; Lei J; Chen R; Chen Z; Xiong Z; Yang L; Jiang M; Zhang H (Journal of Multidisciplinary Healthcare)
Xiaoli Zhu,1,* Juanjuan Lei,2,* Rong Chen,3,* Zhu Chen,4 Zhengchong Xiong,3 Lin Yang,5,* Mengxiao Jiang,6 Huiting Zhang3 1Department of Nursing, Guangzhou Institute of Cancer Research, the Affiliated Cancer Hospital, Guangzhou Medical University, Guangzhou, 510095, People’s Republic of China; 2Department of Surgery, Guangzhou Institute of Cancer Research, the Affiliated Cancer Hospital, Guangzhou Medical University, Guangzhou, 510095, People’s Republic of China; 3Department of Breast Cancer, State Key Laboratory of Oncology in South China, Guangdong Provincial Clinical Research Center for Cancer, Sun Yat-sen University Cancer Center, Guangzhou, 510060, People’s Republic of China; 4Department of Urology, Guangzhou Institute of Cancer Research, the Affiliated Cancer Hospital, Guangzhou Medical University, Guangzhou, 510095, People’s Republic of China; 5Department of Radiation Oncology, Nanfang Hospital, Southern Medical University, Guangzhou, 510515, People’s Republic of China; 6Department of Urology, State Key Laboratory of Oncology in South China,Guangdong Provincial Clinical Research Center for Cancer, Sun Yat-sen University Cancer Center, Guangzhou, 510060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huiting Zhang, Department of Breast Cancer, State Key Laboratory of Oncology in South China, Guangdong Provincial Clinical Research Center for Cancer, Sun Yat-sen University Cancer Center, Guangzhou, 510060, People’s Republic of China, Tel +86 020 87340517, Email zhanght@sysucc.org.cn Mengxiao Jiang, Department of Urology, State Key Laboratory of Oncology in South China, Guangdong Provincial Clinical Research Center for Cancer, Sun Yat-sen University Cancer Center, Guangzhou, 510060, People’s Republic of China, Tel +86 18898534096, Email Jiangmx@sysucc.org.cnPurpose: This study investigates the relationships between breast cancer survivors’ return to work, health literacy, and cancer recurrence fear. By employing structural equation modeling, we examine the mediating effect of health literacy on the interplay between cancer recurrence fear and the ability to return to work.Patients and Methods: We conducted a survey involving 190 breast cancer survivors, utilizing a general information questionnaire, the Concern About Recurrence Scale, and the Health Literacy Management Scale.Results: Our findings indicate that only 54.2% of the participants successfully returned to work. Notably, health literacy was positively correlated with return to work (r=0.315, p< 0.001), whereas fear of cancer recurrence was negatively correlated (r=− 0.268, p< 0.001). The mediation effect model demonstrated a good fit, confirming that health literacy partially mediates the relationship between cancer recurrence fear and return to work (β= − 0.024, p< 0.001).Conclusion: The findings highlight a concerning situation for breast cancer survivors regarding their return to work. Cancer recurrence fear significantly impacts their ability to re-enter the workforce, both directly and indirectly through health literacy. We recommend that healthcare providers focus on alleviating anxiety related to cancer recurrence and enhancing health literacy to support survivors in their reintegration into society.Keywords: breast cancer survivors, return to work, health literacy, cancer recurrence fear, mediating role